Determinanty i współzależności rozwoju regionalnego i globalnego na początku XXI wieku - Żukrowska, Katarzyna (Determinants and Interdependences of Regional and Global Development at the Beginning of 21st Century, 2005)
The paper synthetically presents determinants of regional and global development as well as mutual interdependences of processes which are launched there, shown at wider international background. It presents the sources enabling acceleration of dynamic of economic growth in individual regions as the result of geographic reallocation of production factors. The contents points out that regions, divided into highly developed economies, catching transition economies and underdeveloped regions as the result of geographic reallocation of production factors. The contents points out that regions, divided into highly developed economies, catching transition economies and underdeveloped economies form a net of interdependences based on complementarity. This finding relates to interdependences between regional and global development, which is strongly stimulated by flows of the capital between the triad: Europe, Japan and USA, triad in which each of the angles is surrounded by big group of economies relying on capital and technological transfers from the core. Relations within the triad as well as within the surrounding groups have accelerated, intensified and deepened, what was accompanied by the process of increasing the number of countries engaged in it. The scale of intensification of the processes can be measured with a simple indicator of capital transfers outside the triad. While still in 1985 the outflow of capital from the triad was estimated by UN's WIR at US$ 587 billion, already in 2001 exceeded US$ 4854 billion, what makes in 15 years an over 8 times rise. Inflow of capital has its requirements which embrace convertibility, exchange rate and price stabilization as well as sound state policy. This process is conditioned of will to change what is accompanied often by lack of political power to introduce required changes relies strongly on process of instilulionalization of international relations. EU is one of the most important players in this game, the activities conducted by the European Commission here are supported recently by relations established by European Central Bank, ie. CFA (Communaute Financiere de 1'Afrique) and Cooperation Financiere Africaine. America focuses on establishing Free Trade Area of Americas (FTAA), while Europe is in final phase of launching an association with MERCOSUR. Japan also does not sleep and associates with Oman, Qatar, Korea and Singapore. The whole process is aimed at acceleration of development in all three groups of countries, it is pointed at introducing world-wide regulations concerning standards, protection, social issues, hiring labor, clean technologies, protecting environment etc. All those processes are closely linked with soft elements of security in which wealth of most developed economies can be undermined by social tensions in peripheries. Same danger can be ascribed to lack of proper regulations concerning environment. Dissemination of advanced technologies crowds out use of energy and raw material consuming technologies. Finally, in interdependent cooperative world, which is in process of creation, rare and costly sources of energy can be replaced by less expensive and available ones (read: nuclear) but such a solution has to be proceeded by elimination of terrorist attack on such plants. Such option of interdependent and advantageous for development shape of international relations is strongly stimulated by list of links that occurred among different groups of countries. The paper lists eleven of them, what embrace among others capital, demographic factor, industrial production, aid money, type of specialization, protection of environment, differences in interest rates, creation of wealth, etc. The paper leads to conclusion that regionalization and globalization are two paths which both lead to the same goal which is liberalization of the world economy, which in long run his supposed to equalize the conditions of production world-wide.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 412-422